Glutathione synthesis - Lu, Shelly C. (Biochimica et biophysica acta, 2013)
Glutathione (GSH) is present in all mammalian tissues as the most abundant non-protein thiol that defends against oxidative stress. GSH is also a key determinant of redox signaling, vital in detoxification of xenobiotics, and regulates cell proliferation, apoptosis, immune function, and fibrogenesis. Biosynthesis of GSH occurs in the cytosol in a tightly regulated manner. Key determinants of GSH synthesis are the availability of the sulfur amino acid precursor, cysteine, and the activity of the rate-limiting enzyme, glutamate cysteine ligase (GCL), which is composed of a catalytic (GCLC) and a modifier (GCLM) subunit. The second enzyme of GSH synthesis is GSH synthetase (GS). This review summarizes key functions of GSH and focuses on factors that regulate the biosynthesis of GSH, including pathological conditions where GSH synthesis is dysregulated. GCL subunits and GS are regulated at multiple levels and often in a coordinated manner. Key transcription factors that regulate the expression of these genes include NF-E2 related factor 2 (Nrf2) via the antioxidant response element (ARE), AP-1, and nuclear factor kappa B (NFκB). There is increasing evidence that dysregulation of GSH synthesis contributes to the pathogenesis of many pathological conditions. These include diabetes mellitus, pulmonary and liver fibrosis, alcoholic liver disease, cholestatic liver injury, endotoxemia and drug-resistant tumor cells. GSH is a key antioxidant that also modulates diverse cellular processes. A better understanding of how its synthesis is regulated and dysregulated in disease states may lead to improvement in the treatment of these disorders. This article is part of a Special Issue entitled Cellular functions of glutathione. ► GSH regulates antioxidant defense, growth, death, immune function, and fibrogenesis. ► GSH is synthesized via two enzymatic steps that are regulated at multiple levels. ► GSH synthesis is dysregulated in multiple human diseases.